Research on Personalized Teaching in Smart Classroom Based on Deep Learning - Jing Gao; Normala Ismail; Abdullah Mat Rashid; Fukai Cao (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Personalized instruction in a smart classroom Education has evolved into a vital and effective instrument in the classroom. Smart classroom education is a strategy for focusing curriculum preparation on encouraging students to pursue research ideas. Different subjects necessitate the advancement of research. Smart classroom is studied and the results project since it is the foundation for research in either topic. Micro-courses will also be a supporting learning model for exploring any subject from such a research viewpoint, rather than a full course for just a subject. In this study, we are going to research on Personalized Teaching in Smart Classroom based on Deep Learning. The Back Propagation (BP) algorithm, that is a Deep Learning method, is developed in this study work to enhance research in smart classes.